Follow, Flex, and Flout: A Relational Frame Theory Account of Flexibility in the Context of Rule-Governed Behavior - Alison Stapleton; Conor McCloskey; Louise McHugh (Behavioral Sciences, 2025)
Being able to change what we are doing when a behavior no longer serves us is important for our health and wellbeing. In the context of rule-governed behavior, changing one’s behavior in line with shifting contingencies is often described as being “flexible”, with many basic laboratory experiments operationalizing flexibility as deviations from a given rule that no longer results in reinforcement. And yet flexibility is not just about flouting rules; sometimes, being flexible means persisting. This paper unpacks flexibility in the context of rule-governed behavior from a relational frame theory perspective, outlining applied examples relevant to health behaviors.